2014
DOI: 10.1007/jhep10(2014)035
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring non-compact spin chains

Abstract: We study three-point correlation functions of local operators in planar N = 4 SYM at weak coupling using integrability. We consider correlation functions involving two scalar BPS operators and an operator with spin, in the so called SL(2) sector. At tree level we derive the corresponding structure constant for any such operator. We also conjecture its one loop correction. To check our proposals we analyze the conformal partial wave decomposition of known four-point correlation functions of BPS operators. In pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 77 publications
7
63
0
Order By: Relevance
“…Here we present the calculation of one such correlator whose OPE gives rise to non-symmetric sum rules. Our result has already been communicated to the authors of [1] who used it and found perfect agreement with their integrability prediction.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Here we present the calculation of one such correlator whose OPE gives rise to non-symmetric sum rules. Our result has already been communicated to the authors of [1] who used it and found perfect agreement with their integrability prediction.…”
Section: Introductionsupporting
confidence: 76%
“…The functions Φ (1) , Φ (2) correspond to the so-called one-and two-loop ladder integrals. Their explicit expressions in terms of polylogarithms can be found in [7,8].…”
Section: Jhep11(2014)139mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, as the ladders limit allows for a simpler access to the wrapping corrections, it could also serve as a useful ground to attempt a finite-size resummation of perturbation theory for 3-point correlators [43][44][45][46][47], using Q-functions as building blocks.…”
Section: Jhep12(2016)122mentioning
confidence: 99%